Zoonotic tuberculosis in a high bovine tuberculosis burden area of Ethiopia - Ayalew, Sosina; Habtamu, Getinet; Melese, Fantanesh; Tessema, Bamlak; Ashford, Roland T.; Chothe, Shubhada K.; Aseffa, Abraham; Wood, James L. N.; Berg, Stefan; Mihret, Adane; , for the ETHICOBOTS Consortium; Aseffa, Abraham; et al. (Frontiers in Public Health, 2023)
Background Tuberculosis (TB) is a major cause of ill health and one of the leading causes of death worldwide, caused by species of the Mycobacterium tuberculosis complex (MTBC), with Mycobacterium tuberculosis being the dominant pathogen in humans and Mycobacterium bovis in cattle. Zoonotic transmission of TB (zTB) to humans is frequent particularly where TB prevalence is high in cattle. In this study, we explored the prevalence of zTB in central Ethiopia, an area highly affected by bovine TB (bTB) in cattle. Method A convenient sample of 385 patients with pulmonary tuberculosis (PTB, N = 287) and tuberculous lymphadenitis (TBLN, N = 98) were included in this cross-sectional study in central Ethiopia. Sputum and fine needle aspirate (FNA) samples were obtained from patients with PTB and TBLN, respectively, and cultures were performed using BACTEC™ MGIT™ 960. All culture positive samples were subjected to quantitative PCR (qPCR) assays, targeting IS1081, RD9 and RD4 genomic regions for detection of MTBC, M. tuberculosis and M. bovis, respectively. Results Two hundred and fifty-five out of 385 sampled patients were culture positive and all were isolates identified as MTBC by being positive for the IS1081 assay. Among them, 249 (97.6%) samples had also a positive RD9 result (intact RD9 locus) and were consequently classified as M. tuberculosis. The remaining six (2.4%) isolates were RD4 deficient and thereby classified as M. bovis. Five out of these six M. bovis strains originated from PTB patients whereas one was isolated from a TBLN patient. Occupational risk and the widespread consumption of raw animal products were identified as potential sources of M. bovis infection in humans, and the isolation of M. bovis from PTB patients suggests the possibility of human-to-human transmission, particularly in patients with no known contact history with animals. Conclusion The detected proportion of culture positive cases of 2.4% being M. bovis from this region was higher zTB rate than previously reported for the general population of Ethiopia. Patients with M. bovis infection are more likely to get less efficient TB treatment because M. bovis is inherently resistant to pyrazinamide. MTBC species identification should be performed where M. bovis is common in cattle, especially in patients who have a history of recurrence or treatment failure.